The safety and soundness effects of bank M&A in the EU - Jens Hagendorff; Maria J. Nieto; Larry D. Wall (Federal Reserve Bank of Atlanta, 2012)
This paper studies the impact of European bank mergers and acquisitions on changes in key safety and soundness measures of both acquirers and targets. We find that capitalization, profitability, and liquidity show signs of statistically and economically significant mean reversion for acquirers. Also, acquirers in cross-border deals tended to perform better when their home country prudential supervisors and deposit insurance funding systems were stricter than the target's. For target banks, the most consistent findings from the cross-sectional regressions are that stronger supervision and tougher deposit insurance funding regimes tend to result in positive postmerger changes in liquidity and performance.
Keywords: G21; G34; G28; 330; banks; mergers; Europe